2018
DOI: 10.2196/jmir.9366
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Methods, Tools, and Statistical Approaches in Google Trends Research: Systematic Review

Abstract: BackgroundIn the era of information overload, are big data analytics the answer to access and better manage available knowledge? Over the last decade, the use of Web-based data in public health issues, that is, infodemiology, has been proven useful in assessing various aspects of human behavior. Google Trends is the most popular tool to gather such information, and it has been used in several topics up to this point, with health and medicine being the most focused subject. Web-based behavior is monitored and a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
237
0
29

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 288 publications
(271 citation statements)
references
References 144 publications
5
237
0
29
Order By: Relevance
“…35 One recent systematic review has identified forecasting as an area in particular need of development. 36 Data from Google Trends™ and other search engine repositories will never replace traditional data collection methods for population health. However, with further refinements and constructive dialogue between researchers and Google, search engine data can offer a powerful, real-time tool to assess how population health and health behaviours are changing within society.…”
Section: Where We Go From Here With Google Trends Tmmentioning
confidence: 99%
“…35 One recent systematic review has identified forecasting as an area in particular need of development. 36 Data from Google Trends™ and other search engine repositories will never replace traditional data collection methods for population health. However, with further refinements and constructive dialogue between researchers and Google, search engine data can offer a powerful, real-time tool to assess how population health and health behaviours are changing within society.…”
Section: Where We Go From Here With Google Trends Tmmentioning
confidence: 99%
“…Researchers are able to compare maximum 5 keywords using segments in one try. Studies on GT can be divided into four areas: infectious diseases; mental health, other diseases and general population behavior [11] and mainly are used to examine the seasonality [12].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers can compare a maximum of five keywords using segments in one try. Studies on GT can be divided into four areas-infectious diseases, mental health, other diseases, and general population behavior [45]-and are mainly conducted to examine seasonality [46].…”
Section: Introductionmentioning
confidence: 99%